Socio-Scientific Issues (SSI)-Based E-Module on Indragiri River Pollution and Land Conversion: A Needs Analysis from the Perspective of Biology Teachers at Senior High School - Hasni, Hasni; Supriatno, Bambang; Diana, Sariwulan (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
The low levels of environmental literacy and decision-making skills among senior high school students remain a pressing concern, particularly in regions facing real ecological challenges such as Keritang District, Indragiri Hilir Regency. This study aimed to: (1) describe the current condition of teaching materials used in Biology learning; (2) examine teachers' perspectives on students' environmental literacy and decision-making skills; (3) explore the relevance of local issues as socio-scientific issue (SSI) contexts; and (4) identify teachers' needs regarding the characteristics of an SSI-based e-module. A qualitative approach with a single case study embedded units design was employed, involving three Biology teachers from all active senior high schools (SMA/MA) in Keritang District, selected through total sampling. Data were collected through semi-structured interviews and lesson plan documentation, analyzed using the interactive model of Miles, Huberman, and Saldaña, and validated through source triangulation and member checking. The findings reveal that: (1) the teaching materials currently used do not incorporate local contexts from Keritang District, as indicated by lesson plans that lack integration of area-specific environmental issues; (2) from teachers’ perspectives, students' environmental literacy remains at the awareness level, while their decision-making skills are still limited; (3) the issues such as pollution of the Indragiri River pollution and land conversion are highly relevant as local SSI contexts due to their rich scientific, social, economic, and ethical dimensions; and (4) there are differences in implementation readiness across schools: public high schools are more prepared to use digital e-modules, while private madrasah require printed modules due to limited access to digital devices. Nevertheless, both require teaching materials that include authentic local data, higher-order thinking (HOTS) activities, e-modules accessible offline via smartphones and printable as an alternative, as well as alignment with the curriSculum. These findings represent a needs analysis as the first phase in the development of an e-module, with the design and validation stages planned as subsequent phases. The results of this needs analysis provide an empirical basis for designing a locally grounded SSI-based e-module to improve the quality of Biology learning in Keritang district.